The impact of green credit on energy efficiency from a green innovation perspective: Empirical evidence from China based on a spatial Durbin model - Xingqi Zhao; Sheng Zeng; Xiaojun Ke; Songyu Jiang (Energy Strategy Reviews, 2023)
Green credit plays a pivotal role in maintaining a balance between energy demand and the transition to low-carbon energy sources while considering energy conservation, emission reduction and the 'dual carbon' goal strategies. The SE-SBM model and the spatial Durbin model were used in this study to understand how green credit affects energy efficiency. The empirical approach was based on provincial panel data collected in China from 2005 to 2020. The results indicated that green credit significantly enhanced energy efficiency and had a substantial positive spatial spillover effect beyond the immediate region. Therefore, the enforcement of green credit policies could enhance energy efficiency within the region and concurrently encourage an improvement in energy efficiency in adjacent regions. Furthermore, the study unveiled significant regional disparities in the impact of green credit on the improvement of energy efficiency across the eastern, central and western regions. The green credit policies should be customized to align with the unique circumstances of different regions. Green innovation serves as the primary conduit through which green credit enhances energy efficiency. These insights offer a valuable reference for policymakers seeking to enhance energy efficiency via green credit policies.